Vagus nerve stimulation inhibits cortical spreading depression. Issue 4 (April 2016) - Chen, Shih-Pin; Ay, Ilknur; Lopes de Morais, Andreia; Qin, Tao; Zheng, Yi; Sadeghian, Homa; Oka, Fumiaki; Simon, Bruce; Eikermann-Haerter, Katharina; Ayata, Cenk
Abstract : Abstract: Vagus nerve stimulation has recently been reported to improve symptoms of migraine. Cortical spreading depression is the electrophysiological event underlying migraine aura and is a trigger for headache. We tested whether vagus nerve stimulation inhibits cortical spreading depression to explain its antimigraine effect. Unilateral vagus nerve stimulation was delivered either noninvasively through the skin or directly by electrodes placed around the nerve. Systemic physiology was monitored throughout the study. Both noninvasive transcutaneous and invasive direct vagus nerve stimulations significantly suppressed spreading depression susceptibility in the occipital cortex in rats. The electrical stimulation threshold to evoke a spreading depression was elevated by more than 2-fold, the frequency of spreading depressions during continuous topical 1 M KCl was reduced by ∼40%, and propagation speed of spreading depression was reduced by ∼15%. This effect developed within 30 minutes after vagus nerve stimulation and persisted for more than 3 hours. Noninvasive transcutaneous vagus nerve stimulation was as efficacious as direct invasive vagus nerve stimulation, and the efficacy did not differ between the ipsilateral and contralateral hemispheres. Our findings provide a potential mechanism by which vagus nerve stimulation may be efficacious in migraine and suggest that susceptibility to spreading depression is a suitable platform to optimize its efficacy. Abstract : Supplemental Digital Content is Available in the Text.Vagus nerve stimulation is a novel nonpharmacologic treatment in migraine, the mechanism of which might be mediated by suppressing the susceptibility to cortical spreading depression.